Thermodonor activation energy and mechanisms of tensoeffects in transmutation-doped y-irradiated silicon - Dotsenko, Yu.P.; Ermakov, V.M.; Gorin, A.E.; Khivrych, V.I.; Kolomoets, V.V.; Machulin, V.F.; Panasjuk, L.I.; Prokopenko, I.V.; Sus', B.B.; Venger, E.F. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2003)
Activation energy of high temperature technological thermodonors (TD) has been determined in transmutation-doped n-Si(P) using the data analysis of the Hall-effect temperature dependence. Physical mechanisms of tensoeffects in n-Si(P) crystals doped by neutron irradiation and doped at growth were studied by the tensoeffects measurements and by analysis of the pressure dependencies of the electron concentration ratio in "upper" and "lower" L1-valleys of uniaxially strained samples. Comparison of the some parameters for the crystals doped either by neutron transmutation method or in the melt is carried out.